Preparation and Properties of Antitumor Drug Based on Lipid Derivative of Sarcolysin - Tereshkina, Yu.A.; Sanzhakov, M.A.; Kostryukova, L.V.; Korotkevich, E.I.; Chistov, A.A.; Tikhonova, E.G.; Prozorovsky, V.N.; Ipatova, O.M. (Biomedical Chemistry: Research and Methods, 2019)
The conditions for the preparation of a drug formulations based on the lipid derivative of sarcolysin embedded in phospholipid nanoparticles have been optimized. The drug is an ultra-thin emulsion with a light transmittance above 80% and a particle size of not more than 50 nm. It should be noted that 99% of the lipid derivative of sarcolysin are incorporated into phospholipid nanoparticles. Preservation of aggregation stability in the aquatic environment was observed for at least 2 days. In vitro experiments have shown that sarcolysin, introduced as a part of phospholipid nanoparticles, is distributed among lipoproteins and protein components of plasma. Moreover, the content of sarcolysin in all fractions involved in the transport of biologically active substances in the body, is significantly higher in case of prodrug administration (lipid derivative of sarcolysin) in the composition of phospholipid nanoparticles than, as compared with administration of a free form (pharmacological substances) to the incubation medium. The transformation of a prodrug into the drug sarcolysin occurs in the blood cells.